Polyethylene Terephthalate Modified Asphalt Concrete with Blended Recycled Aggregates: Analysis and Assessment - Suddeepong, Apichat; Akkharawongwhatthana, Kongsak; Horpibulsuk, Suksun; Buritatum, Apinun; Hoy, Menglim; Yaowarat, Teerasak; Pongsri, Nantipat; Chinkulkijniwat, Avirut; Arulrajah, Arul; Horpibulsuk, Jitwadee (Civil Engineering Journal, 2024)
The research study attempts to ascertain the mechanical performance of asphalt concrete, using reclaimed asphalt concrete pavement (RAP) and recycled concrete aggregate (RCA) blends with polyethylene terephthalate (PET) as a modifier. The influence factors were evaluated, including RAP/RCA ratios and PET contents on static and cyclic performances. The static performance was assessed through the indirect tensile strength (ITS) tests, while the cyclic performance was assessed through the indirect tensile resilient modulus (ITMR), indirect tensile fatigue life (ITFL), and wheel tracking tests. Compared to asphalt concrete using natural aggregate (NA), the ITMR of RAP-RCA-PET asphalt concretes was higher when PET contents were between 0.2% and 0.6% for RAP/RCA = 80/20. The ITFL of RAP-RCA-PET asphalt concretes was found to be higher than that of NA asphalt concrete when PET contents ranged from 0.2% to 0.6% for RAP/RCA < 90/10. The ITFL was also higher when PET content was between 0.4% and 0.6% for RAP/RCA = 100/0. RAP-RCA-PET asphalt concretes exhibited lower rut depth than NA asphalt concrete with RAP/RCA = 90/10 and 60/40 at PET contents of 0.4% to 1.0% and with RAP/RCA = 80/20 at PET contents of 0.2% to 1.0%. The RAP/RCA = 80/20 and PET content = 0.6% were found to be the best ingredient in term of both fatigue cracking and rutting resistances. As per the systematic analysis, the fatigue distress models of RAP-RCA-PET asphalt concretes for various PET contents were developed in term of ITFL and tensile strain (????????) relationship and useful for mechanistic design. The results of this research will contribute to promoting RAP-RCA-PET asphalt concrete as a greener material in pavement construction. Doi: 10.28991/CEJ-2024-010-11-08 Full Text: PDF